Experimental investigation into effects of material and energy regulation of debris flow by using check dams with different porosities - Huang, Jinyan; Liu, Xingrong; Zhang, Zuoxiong; Zhang, Jinxia; Ma, Yanjie; Li, Qirun; Wang, Yukun; An, Yapen (Frontiers in Earth Science, 2024)
The design of check dam openings for debris flow control has been identified as a longstanding challenge, with no definitive solution yet identified. In this study, a quantitative analysis of the control efficacy of check dams with varying opening rates is presented. Field investigation data of 67 check dams located in Wenxian County, Gansu Province, were utilized to gain a preliminary understanding of their running state and damage situation. Building upon this, five check dams with opening rates ranging from 2.1% to 10.4% were designed and subjected to testing. Parameters including volumetric water content, pore water pressure, deposit morphology, and particle size distribution were analyzed to investigate the effect of varying opening rates on debris flow control. The results showed that: 1) As the opening rate of the check dams increased, the peaks of volumetric water content and pore water pressure behind the dam first decreased and then stabilized. When the opening rate was increased to 6.3% or higher, these parameters reached stable values. 2) Check dams with different opening rates all demonstrated good effects in retaining the coarse and sluicing the fine, resulting in the average particle size behind dams was coarsened by 2.65 times. This coarsening was primarily attributed to an increase in the proportion of retained particles within the 2–5 mm size range. 3) An optimal opening range of 4.2%–6.3% was identified for effective debris flow control. Compared with other dams, Dam II with opening rate 4.2% exhibited superior performance in mitigating flow energy and intercepting coarse particles, but it imposed stringent strength-related requirements.